High-insulation polyimide composite film precursor solution and film preparation method thereof
By using carbon nanotubes and mica to prepare modified carbon nanotube composites, the problem of degradation of insulation performance in traditional polyimide films under high electric fields is solved, the high insulation and corona resistance performance is improved, and the application range of polyimide films is expanded.
Patent Information
- Application Number
- CN202510025701.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional polyimide films are prone to partial discharge, corona and other phenomena in high electric field strength environments, resulting in a degradation of insulation performance and difficult to meet the application scenarios where high insulation requirements are required.
The modified carbon nanotube composite is prepared by using carbon nanotubes and mica as raw materials, and a high-insulating polyimide composite film is prepared through this composite material. The good insulation performance and thermal stability of mica are used to improve the insulation performance and corona resistance of the film.
It significantly improves the insulation performance and corona resistance of high-insulation polyimide composite films, and broadens its application range in high-voltage insulation, high-end electronics and other fields.
Smart Images

Figure CN119798737A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of insulating materials, and in particular relates to a high-insulation polyimide composite film precursor solution and a film preparation method thereof. Background Art
[0002] As a high-performance organic polymer material, polyimide (PI) has many excellent properties, such as high temperature resistance, chemical corrosion resistance, good mechanical properties and excellent insulation. It has extremely wide and critical applications in many fields such as aerospace, electronics, microelectronics, and new energy. It is usually prepared from a precursor solution through a series of processing steps, such as coating, thermal imidization and other processes to form the final polyimide film product. Although polyimide itself has certain insulation properties, with the rapid development of modern science and technology, in some specific application scenarios with extremely high requirements for insulation performance, traditional polyimide films have gradually been unable to meet the needs. For example, the products generally have low and unstable breakdown voltage and corona resistance performance indicators, which seriously affects the reliability of product use. Indicators such as mechanical properties are also not high, and there is still a lot of room for improvement in the technical indicators and quality of the products.
[0003] At present, conventional polyimide films often have relatively simple molecular structures and compositions. Under high electric field strength environments, they may experience local discharge, corona and other phenomena, resulting in a decrease in insulation performance. This greatly limits the further expansion of polyimide film applications in fields with high insulation requirements.
[0004] Based on the above problems, this application document proposes a high-insulation polyimide composite film precursor solution and a film preparation method thereof, so as to broaden the application scope of polyimide film in key fields such as high-voltage insulation and high-end electronics, and promote the further development of related industries. Summary of the invention
[0005] The purpose of the present invention is to provide a high-insulation polyimide composite film precursor solution and a film preparation method thereof. In the process of preparing the high-insulation polyimide composite film, carbon nanotubes and mica are used as raw materials to prepare a modified carbon nanotube composite material. The mica with good insulation performance and thermal stability is used to further improve the insulation performance and corona resistance of the high-insulation polyimide composite film.
[0006] The technical solution adopted by the present invention is as follows:
[0007] A highly insulating polyimide composite film precursor solution and a film preparation method thereof, comprising the following steps:
[0008] Stp100: Preparation of modified carbon nanotube composites:
[0009] The carbon nanotubes are sequentially subjected to acid treatment and polymer wrapping to obtain modified carbon nanotubes, and the modified carbon nanotubes are dispersed in water to obtain a suspension; the mica powder is pretreated, the pretreated mica powder is added to the suspension, ultrasonically treated for 1 to 2 hours, stirred for 0.5 to 1 hour, and a mixed suspension is obtained; the mixed suspension is rotary evaporated to obtain a modified carbon nanotube composite, wherein the weight ratio of the modified carbon nanotubes, the mica powder and the water in the mixed suspension is 1:1:100;
[0010] Stp200: prepare precursor solution;
[0011] The modified carbon nanotube composite material is dispersed in an organic solvent, a protective gas is introduced, ultrasonic treatment is performed for 1 to 2 hours, and stirring is performed for 0.5 to 1 hour to obtain a first mixed solution. A diamine monomer is added to the first mixed solution, and stirring is performed for 0.5 to 1 hour to obtain a second mixed solution. Under the protection of the protective gas, a dianhydride monomer is added to the second mixed solution, and stirring is performed at room temperature for 4 to 8 hours to obtain a precursor solution.
[0012] Stp300: Preparation of high insulation polyimide composite film:
[0013] The precursor solution was coated onto a glass plate, which was placed in a drying device and dried at 70°C for 9 hours. The temperature was increased in a stepwise manner, and the glass plate was dried at 100°C, 150°C, 200°C, and 300°C for 1 hour. After drying, the glass plate was cooled to room temperature and demolded with deionized water to obtain a highly insulating polyimide composite film.
[0014] In a preferred embodiment, in the Stp100, the carbon nanotubes are multi-walled carbon nanotubes.
[0015] In a preferred embodiment, in Stp100, the carbon nanotubes are sequentially subjected to acid treatment and polymer wrapping, comprising the following steps:
[0016] Stp101: Mix concentrated sulfuric acid and concentrated nitric acid to obtain a mixed acid solution, wherein the volume ratio of the concentrated sulfuric acid to the concentrated nitric acid is 3:1;
[0017] Stp102: dispersing carbon nanotubes in a mixed acid solution, and subjecting the carbon nanotubes to an acid treatment at 45kHz ultrasonic treatment for 1 to 2 hours, wherein the weight ratio of the carbon nanotubes to the mixed acid solution is 1:400;
[0018] Stp103: The acid-treated carbon nanotubes were washed with deionized water for multiple times and vacuum dried at 60°C to 80°C for 24 h to obtain acidified carbon nanotubes;
[0019] Stp104: dissolving the polymer in a solvent to obtain a polymer solution, dispersing the acidified carbon nanotubes in the polymer solution, ultrasonically treating for 1 to 2 hours, removing the solvent, and obtaining modified carbon nanotubes.
[0020] In a preferred embodiment, in Stp104, the polymer is one of the following substances: polystyrene, polypropylene; and the solvent is one of the following substances: toluene, chloroform.
[0021] In a preferred embodiment, in Stp100, the mica powder is pretreated, comprising the following steps:
[0022] Stp110: dissolving the surfactant in water to obtain a pretreatment solution;
[0023] Stp111: Disperse mica powder in the pretreatment liquid, perform ultrasonic treatment for 0.5-1h, stir for 0.5-1h, and centrifuge to obtain mica powder wet material;
[0024] Stp112: Wash the wet mica powder with deionized water for 3 to 5 times to remove the residual surfactant on the surface of the wet mica powder, and vacuum dry it at 60°C to 80°C for 2 to 4 hours to obtain pretreated mica powder.
[0025] In a preferred embodiment, in Stp110, the surfactant is one of the following substances: sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, and the weight ratio of the surfactant to water is 1:100.
[0026] In a preferred embodiment, in the Stp111, the particle size of the mica powder is in the range of 10 to 100 nm.
[0027] In a preferred embodiment, in the Stp200, the organic solvent is N,N-dimethylacetamide, the protective gas is nitrogen, the diamine monomer is one of the following substances: 4,4'-hexafluoroisopropylphthalic anhydride, 4,4'-bisphenol A diamine, 4,4'-biphenyl ether diamine, 4,4'-diaminodiphenylmethane, and the dianhydride monomer is one or more of the following substances: 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 4,4'-oxydiphthalic anhydride, and pyromellitic acid dianhydride.
[0028] In a preferred embodiment, in Stp200, the molar ratio of the diamine monomer to the dianhydride monomer is 1:1.
[0029] The technical effects achieved by the present invention are:
[0030] In the process of preparing the high-insulation polyimide composite film, the present invention uses carbon nanotubes and mica as raw materials to prepare a modified carbon nanotube composite material, and uses mica with good insulation performance and thermal stability to further improve the insulation performance and corona resistance of the high-insulation polyimide composite film, so as to broaden the application scope of the polyimide film in key fields such as high-voltage insulation and high-end electronics;
[0031] The present invention introduces active groups on the surface of carbon nanotubes by acid treatment to increase the surface activity of carbon nanotubes, and then wraps the carbon nanotubes with polymers to effectively prevent direct contact between carbon nanotubes, thereby reducing agglomeration and facilitating the adsorption of mica powder by carbon nanotubes, so that mica and carbon nanotubes can be evenly dispersed in the high-insulation polyimide composite film. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 is a SEM image of the high-insulation polyimide composite film prepared in Example 2 of the present invention;
[0033] Figure 2 It is a schematic diagram of the mechanical properties of the high-insulation polyimide composite film of the present invention;
[0034] Figure 3 It is a schematic diagram of the change of resistivity of the high-insulation polyimide composite film with voltage in the present invention;
[0035] Figure 4 Schematic diagram of the change of dielectric constant of the high-insulation polyimide composite film with frequency in the present invention;
[0036] Figure 5 Schematic diagram of the change of dielectric loss of the high-insulation polyimide composite film with frequency in the present invention;
[0037] Figure 6 This is a graph showing the corona resistance life test results of the high-insulation polyimide composite film of the present invention. DETAILED DESCRIPTION
[0038] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the accompanying drawings.
[0039] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0040] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure or characteristic that may be included in at least one implementation of the present invention. The phrase "in a preferred embodiment" that appears in different places in this specification does not refer to the same embodiment, nor is it a separate or selective embodiment that is mutually exclusive with other embodiments.
[0041] Preparation Example
[0042] Preparation Example 1
[0043] Preparation of mixed acid:
[0044] Concentrated sulfuric acid and concentrated nitric acid were mixed in a volume ratio of 3:1 to obtain a mixed acid solution.
[0045] Preparation Example 2
[0046] Preparation of polymer solution:
[0047] The polymer and the solvent were mixed at a weight ratio of 1:100 and stirred for 0.5 h to obtain a polymer solution;
[0048] The polymer is one of the following substances: polystyrene, polypropylene; the solvent is one of the following substances: toluene, chloroform. In this preparation example, the polymer is preferably polystyrene, and the solvent is preferably toluene.
[0049] Preparation Example 3
[0050] Mica powder pretreatment:
[0051] A surfactant and water are mixed in a weight ratio of 1:100 to prepare a pretreatment liquid, mica powder with a particle size range of 10 to 100 nm is dispersed in the pretreatment liquid, ultrasonically treated at 40 kHz for 0.5 to 1 hour, stirred for 0.5 to 1 hour, and centrifuged through a centrifugal device to obtain a wet mica powder material, and then the wet mica powder material is repeatedly washed 4 times with deionized water to remove the residual surfactant on the surface of the wet mica powder material, and vacuum dried at 80°C for 4 hours to obtain a pretreated mica powder, wherein the surfactant is one of the following substances: sodium dodecyl sulfate, hexadecyltrimethylammonium bromide. In this preparation example, the surfactant is preferably sodium dodecyl sulfate.
[0052] Example
[0053] Embodiment 1
[0054] Step 1: Preparation of modified carbon nanotube composites:
[0055] Take 10g of carbon nanotubes and disperse them in 500ml of mixed acid solution, treat them ultrasonically at 45kHz for 1h, add deionized water to dilute it ten times, filter it through a mixed fiber microfiltration membrane, wash it repeatedly with deionized water until it is neutral, and vacuum dry it at 60℃ for 24h to obtain acidified carbon nanotubes; take 10g of acidified carbon nanotubes and disperse them in 1L of polymer solution, treat them ultrasonically at 40kHz for 1h, remove the solvent by evaporation or reduced pressure distillation to obtain modified carbon nanotubes; take 10g of modified carbon nanotubes and disperse them in 1L of water to obtain a suspension, then disperse 10g of pretreated mica powder in the suspension, treat it ultrasonically at 40kHz for 1h, stir for 0.5h to obtain a mixed suspension, and rotary evaporate the mixed suspension to obtain a modified carbon nanotube composite, wherein the carbon nanotubes are multi-walled carbon nanotubes with a diameter range of 40 to 60nm and a length of 0.5 to 40μm, and the carbon nanotubes are treated with a mixed acid solution;
[0056] The carbon nanotubes are first treated with acid, then wrapped with polymers, and finally mixed with mica powder. First, active groups such as carboxyl and hydroxyl groups are introduced on the surface of the carbon nanotubes through acid treatment. These groups can increase the hydrophilicity of the carbon nanotubes, thereby improving their dispersibility in aqueous solutions and increasing the surface activity of the carbon nanotubes. The surface of the carbon nanotubes after acid treatment has more active sites for adsorption. The subsequent polymer wrapping can effectively prevent direct contact between the carbon nanotubes, thereby reducing agglomeration. At the same time, the dispersibility and stability of mica powder on the surface of the carbon nanotubes can be further improved, which is helpful to form a more uniform composite material, improve the interaction force between the modified carbon nanotubes and the mica powder, and is conducive to improving the adsorption capacity of the carbon nanotubes on the mica powder. At the same time, due to the stable crystal structure of mica, it has good insulation performance, thermal stability and mechanical properties, and can maintain a good insulation state under high electric field strength, thereby reducing the occurrence of corona discharge.
[0057] Step 2: Prepare the precursor solution:
[0058] Nitrogen was introduced into the container and 100 ml of N,N-dimethylacetamide with a mass fraction of 99.8% was added, 2.36 g of the modified carbon nanotube composite was dispersed in N,N-dimethylacetamide, ultrasonic treatment was performed for 2 h, and stirring was performed for 1 h to obtain a first mixed solution, 6.5 g of 4,4′-hexafluoroisopropylphthalic anhydride was added to the first mixed solution, and stirring was performed for 0.5 h to obtain a second mixed solution, and 6.5 g of 2,2′-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride was added to the second mixed solution under nitrogen protection, and stirring was performed at room temperature for 8 h, and the solution was placed in a vacuum drying device to remove bubbles to obtain a precursor solution, wherein the mass fraction of the modified carbon nanotube composite was 2%;
[0059] Step 3: Preparation of high insulation polyimide composite film:
[0060] The precursor solution was coated onto a glass plate, which was placed in a drying device and dried at 70°C for 9 hours. The temperature was increased in a stepwise manner, and the glass plate was dried at 100°C, 150°C, 200°C, and 300°C for 1 hour. After drying, the glass plate was cooled to room temperature and demolded with deionized water to obtain a highly insulating polyimide composite film.
[0061] Embodiment 2
[0062] Step 1: Preparation of modified carbon nanotube composites:
[0063] 10g of carbon nanotubes were dispersed in 500ml of mixed acid solution, ultrasonically treated at 45kHz for 1h, deionized water was added to dilute ten times, filtered through a mixed fiber microfiltration membrane, repeatedly washed with deionized water for multiple times until neutral, and vacuum dried at 60°C for 24h to obtain acidified carbon nanotubes; 10g of acidified carbon nanotubes were dispersed in 1L of polymer solution, ultrasonically treated at 40kHz for 1h, and the solvent was removed by evaporation or reduced pressure distillation to obtain modified carbon nanotubes; 10g of modified carbon nanotubes were dispersed in 1L of water to obtain a suspension, and 10g of pretreated mica powder was dispersed in the suspension, ultrasonically treated at 40kHz for 1h, stirred for 0.5h, and a mixed suspension was obtained, and the mixed suspension was rotary evaporated to obtain a modified carbon nanotube composite, wherein the carbon nanotubes were multi-walled carbon nanotubes with a diameter range of 40 to 60nm and a length of 0.5 to 40μm;
[0064] Step 2: Prepare the precursor solution:
[0065] Nitrogen was introduced into the container and 100 ml of N,N-dimethylacetamide with a mass fraction of 99.8% was added, 3.54 g of the modified carbon nanotube composite was dispersed in the N,N-dimethylacetamide, ultrasonic treatment was performed for 2 h, and stirring was performed for 1 h to obtain a first mixed solution, 6.5 g of 4,4′-bisphenol A diamine was added to the first mixed solution, and stirring was performed for 0.5 h to obtain a second mixed solution, and 6.5 g of 3,3',4,4'-biphenyltetracarboxylic dianhydride was added to the second mixed solution under nitrogen protection, and stirring was performed at room temperature for 8 h, and the solution was placed in a vacuum drying device to remove bubbles to obtain a precursor solution, wherein the mass fraction of the modified carbon nanotube composite was 3%;
[0066] Step 3: Preparation of high insulation polyimide composite film:
[0067] The precursor solution was coated onto a glass plate, which was placed in a drying device and dried at 70°C for 9 hours. The temperature was increased in a stepwise manner, and the glass plate was dried at 100°C, 150°C, 200°C, and 300°C for 1 hour. After drying, the glass plate was cooled to room temperature and demolded with deionized water to obtain a highly insulating polyimide composite film.
[0068] Embodiment 3
[0069] Step 1: Preparation of modified carbon nanotube composites:
[0070] 10g of carbon nanotubes were dispersed in 500ml of mixed acid solution, ultrasonically treated at 45kHz for 1h, deionized water was added to dilute ten times, filtered through a mixed fiber microfiltration membrane, repeatedly washed with deionized water for multiple times until neutral, and vacuum dried at 60°C for 24h to obtain acidified carbon nanotubes; 10g of acidified carbon nanotubes were dispersed in 1L of polymer solution, ultrasonically treated at 40kHz for 1h, and the solvent was removed by evaporation or reduced pressure distillation to obtain modified carbon nanotubes; 10g of modified carbon nanotubes were dispersed in 1L of water to obtain a suspension, and 10g of pretreated mica powder was dispersed in the suspension, ultrasonically treated at 40kHz for 1h, stirred for 0.5h, and a mixed suspension was obtained, and the mixed suspension was rotary evaporated to obtain a modified carbon nanotube composite, wherein the carbon nanotubes were multi-walled carbon nanotubes with a diameter range of 40 to 60nm and a length of 0.5 to 40μm;
[0071] Step 2: Prepare the precursor solution:
[0072] Nitrogen was introduced into the container and 100 ml of N,N-dimethylacetamide with a mass fraction of 99.8% was added, 4.72 g of the modified carbon nanotube composite was dispersed in N,N-dimethylacetamide, ultrasonically treated for 2 h, stirred for 1 h, and a first mixed solution was obtained. 6.5 g of 4,4′-biphenyl ether diamine was added to the first mixed solution, and stirred for 0.5 h to obtain a second mixed solution. Under nitrogen protection, 6.5 g of 4,4′-oxydiphthalic anhydride was added to the second mixed solution, stirred at room temperature for 8 h, and placed in a vacuum drying device to remove bubbles to obtain a precursor solution, wherein the mass fraction of the modified carbon nanotube composite was 4%;
[0073] Step 3: Preparation of high insulation polyimide composite film:
[0074] The precursor solution was coated onto a glass plate, which was placed in a drying device and dried at 70°C for 9 hours. The temperature was increased in a stepwise manner, and the glass plate was dried at 100°C, 150°C, 200°C, and 300°C for 1 hour. After drying, the glass plate was cooled to room temperature and demolded with deionized water to obtain a highly insulating polyimide composite film.
[0075] Embodiment 4
[0076] Step 1: Preparation of modified carbon nanotube composites:
[0077] 10g of carbon nanotubes were dispersed in 500ml of mixed acid solution, ultrasonically treated at 45kHz for 1h, deionized water was added to dilute ten times, filtered through a mixed fiber microfiltration membrane, repeatedly washed with deionized water for multiple times until neutral, and vacuum dried at 60°C for 24h to obtain acidified carbon nanotubes; 10g of acidified carbon nanotubes were dispersed in 1L of polymer solution, ultrasonically treated at 40kHz for 1h, and the solvent was removed by evaporation or reduced pressure distillation to obtain modified carbon nanotubes; 10g of modified carbon nanotubes were dispersed in 1L of water to obtain a suspension, and 10g of pretreated mica powder was dispersed in the suspension, ultrasonically treated at 40kHz for 1h, stirred for 0.5h, and a mixed suspension was obtained, and the mixed suspension was rotary evaporated to obtain a modified carbon nanotube composite, wherein the carbon nanotubes were multi-walled carbon nanotubes with a diameter range of 40 to 60nm and a length of 0.5 to 40μm;
[0078] Step 2: Prepare the precursor solution:
[0079] Nitrogen was introduced into the container and 100 ml of N,N-dimethylacetamide with a mass fraction of 99.8% was added, 5.9 g of the modified carbon nanotube composite was dispersed in the N,N-dimethylacetamide, ultrasonically treated for 2 h, stirred for 1 h, and a first mixed solution was obtained. 6.5 g of 4,4′-diaminodiphenylmethane was added to the first mixed solution, and stirred for 0.5 h to obtain a second mixed solution. Under nitrogen protection, 6.5 g of pyromellitic dianhydride was added to the second mixed solution, stirred at room temperature for 8 h, and placed in a vacuum drying device to remove bubbles to obtain a precursor solution, wherein the mass fraction of the modified carbon nanotube composite was 5%;
[0080] Step 3: Preparation of high insulation polyimide composite film:
[0081] The precursor solution was coated onto a glass plate, which was placed in a drying device and dried at 70°C for 9 hours. The temperature was increased in a stepwise manner, and the glass plate was dried at 100°C, 150°C, 200°C, and 300°C for 1 hour. After drying, the glass plate was cooled to room temperature and demolded with deionized water to obtain a highly insulating polyimide composite film.
[0082] Comparative Example
[0083] Comparative Example 1
[0084] This comparative example is based on Example 1, and only the carbon nanotubes are treated with acid. Specifically:
[0085] Step 1: Preparation of acidified carbon nanotubes:
[0086] 10 g of carbon nanotubes were dispersed in 500 ml of mixed acid solution, ultrasonically treated at 45 kHz for 1 hour, diluted ten times with deionized water, filtered through a mixed fiber microfiltration membrane, repeatedly washed with deionized water for several times until neutral, and vacuum dried at 60 ° C for 24 hours to obtain acidified carbon nanotubes, wherein the carbon nanotubes are multi-walled carbon nanotubes with a diameter range of 40 to 60 nm and a length of 0.5 to 40 μm;
[0087] Step 2: Prepare the precursor solution:
[0088] Nitrogen was introduced into the container and 100 ml of N,N-dimethylacetamide with a mass fraction of 99.8% was added, 2.36 g of acidified carbon nanotubes were dispersed in N,N-dimethylacetamide, ultrasonic treatment was performed for 2 h, and stirring was performed for 1 h to obtain a first mixed solution, 6.5 g of 4,4′-hexafluoroisopropylphthalic anhydride was added to the first mixed solution, and stirring was performed for 0.5 h to obtain a second mixed solution, and 6.5 g of 2,2′-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride was added to the second mixed solution under nitrogen protection, and stirring was performed at room temperature for 8 h, and the mixture was placed in a vacuum drying device to remove bubbles to obtain a precursor solution, wherein the mass fraction of the acidified carbon nanotubes was 3%;
[0089] Step 3: Preparation of high insulation polyimide composite film:
[0090] The precursor solution was coated onto a glass plate, which was placed in a drying device and dried at 70°C for 9 hours. The temperature was increased in a stepwise manner, and the glass plate was dried at 100°C, 150°C, 200°C, and 300°C for 1 hour. After drying, the glass plate was cooled to room temperature and demolded with deionized water to obtain a highly insulating polyimide composite film.
[0091] Comparative Example 2
[0092] This comparative example is based on Example 2, except that the carbon nanotubes are only acid treated and polymer coated without adding mica powder. Specifically:
[0093] Step 1: Preparation of modified carbon nanotubes:
[0094] 10g of carbon nanotubes were dispersed in 500ml of mixed acid solution, ultrasonically treated at 45kHz for 1h, diluted ten times with deionized water, filtered through a mixed fiber microfiltration membrane, repeatedly washed with deionized water for multiple times until neutral, and vacuum dried at 60°C for 24h to obtain acidified carbon nanotubes; 10g of acidified carbon nanotubes were dispersed in 1L of polymer solution, ultrasonically treated at 40kHz for 1h, and the solvent was removed by evaporation or reduced pressure distillation to obtain modified carbon nanotubes, wherein the carbon nanotubes were multi-walled carbon nanotubes with a diameter range of 40 to 60nm and a length of 0.5 to 40μm;
[0095] Step 2: Prepare the precursor solution:
[0096] Nitrogen was introduced into the container and 100 ml of N,N-dimethylacetamide with a mass fraction of 99.8% was added, 3.54 g of modified carbon nanotubes were dispersed in N,N-dimethylacetamide, ultrasonic treatment was performed for 2 h, and stirring was performed for 1 h to obtain a first mixed solution, 6.5 g of 4,4′-bisphenol A diamine was added to the first mixed solution, and stirring was performed for 0.5 h to obtain a second mixed solution, and 6.5 g of 3,3',4,4'-biphenyltetracarboxylic dianhydride was added to the second mixed solution under nitrogen protection, and stirring was performed at room temperature for 8 h, and the solution was placed in a vacuum drying device to remove bubbles to obtain a precursor solution, wherein the mass fraction of the modified carbon nanotubes was 3%;
[0097] Step 3: Preparation of high insulation polyimide composite film:
[0098] The precursor solution was coated onto a glass plate, which was placed in a drying device and dried at 70°C for 9 hours. The temperature was increased in a stepwise manner, and the glass plate was dried at 100°C, 150°C, 200°C, and 300°C for 1 hour. After drying, the glass plate was cooled to room temperature and demolded with deionized water to obtain a highly insulating polyimide composite film.
[0099] Figure 1 This is a SEM image of the high-insulation polyimide composite film prepared in Example 2;
[0100] from Figure 1 It can be seen that in the high-insulation polyimide composite film prepared in Example 2, the modified carbon nanotube composite material is evenly distributed in the polyimide, with less agglomeration.
[0101] Figure 2 Schematic diagram of the mechanical properties of high insulation polyimide composite film, where: Figure 2 a is a curve showing the variation of elongation at break versus tensile strength of the highly insulating polyimide composite film prepared in Example 1; Figure 2 b is a curve showing the variation of elongation at break versus tensile strength of the high-insulation polyimide composite film prepared in Example 2; Figure 2 c is a curve showing the variation of elongation at break versus tensile strength of the high-insulation polyimide composite film prepared in Example 3; Figure 2 d is a curve showing the variation of elongation at break versus tensile strength of the high-insulation polyimide composite film prepared in Example 4; Figure 2 Figure e is a curve showing the variation of elongation at break versus tensile strength of the highly insulating polyimide composite film prepared in Comparative Example 1; Figure 2f is the variation curve of elongation at break of the high insulation polyimide composite film prepared in comparative example 2 with tensile strength; referring to GB / T1040.3-2006 standard "Test method for tensile properties of plastics", samples of high insulation polyimide composite film were cut, and mechanical properties were tested by tensile testing machine and the results were recorded, combined with Figure 2 It can be seen that the high-insulation polyimide composite film samples prepared in Examples 1 to 4 through acid treatment, polymer wrapping, mica mixing and other process treatments on the carbon nanotubes have higher comprehensive performance in mechanical properties than the high-insulation polyimide composite films prepared in Comparative Examples 1 to 2. Combining Examples 1 to 4, it can be seen that when the acidified carbon nanotube content is 3% (ie, Example 2), the tensile strength and elongation at break of the high-insulation polyimide composite film reach the maximum value. Combining the above data, the high-insulation polyimide composite film prepared in Example 2 has the best mechanical properties.
[0102] Figure 3 is a schematic diagram of the change of resistivity with voltage. Figure 3 It can be seen that the high-insulating polyimide composite film prepared in Examples 1 to 4, after adding mica, has a resistivity significantly higher than the resistivity of the high-insulating polyimide composite film prepared in Comparative Example 1 and Comparative Example 2 under the same voltage. Combined with the resistivity of Examples 1 to 4, it can be seen that the high-insulating polyimide composite film prepared in Example 2 is superior to the high-insulating polyimide composite films prepared in Examples 1, 3 and 4.
[0103] Figure 4 Schematic diagram of the change of dielectric constant with frequency. Figure 5 The schematic diagram of the change of dielectric loss with frequency is shown in Figure 2. Figure 4 and Figure 5 It can be seen that the high-insulation polyimide composite films prepared in Comparative Examples 1 and 2 have higher dielectric constants and dielectric losses at the same frequency, and are more easily polarized under the action of an electric field, so that more polarized charges can be generated inside. These polarized charges will affect the electric field distribution to a certain extent, and may be easier to conduct current, or the obstruction to the electric field is relatively reduced. After adding mica, the high-insulation polyimide composite films prepared in Examples 1 to 4 have a dielectric constant and a dielectric loss that are lower than those of the high-insulation polyimide composite films prepared in Comparative Examples 1 and 2 (that is, the insulation performance is improved). At the same time, combined with the dielectric constants and dielectric losses of Examples 1 to 4, it can be seen that when the content of the modified carbon nanotube composite material in the high-insulation polyimide composite film is 3%, its insulation performance is best. In general, the insulation performance of the high-insulation polyimide composite film prepared in Example 2 is better.
[0104] Figure 6 This is the result of the corona resistance life test. According to the GB / T13542.2-2009 standard "Electrical Insulation Film Part 2: Test Method", high insulation polyimide composite film samples were cut to conduct corona resistance life test and record the results. Figure 6 It can be seen that the high-insulation polyimide composite film prepared in Examples 1 to 4 has a corona resistance life that is significantly higher than the corona resistance life of the high-insulation polyimide composite film prepared in Comparative Examples 1 and 2. At the same time, among Examples 1 to 4, the corona resistance life in Example 3 is the best. However, based on various data, the comprehensive performance of the high-insulation polyimide composite film prepared in Example 2 is better.
[0105] The above is only a preferred embodiment of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made without departing from the principles of the present invention, and these improvements and modifications should also be considered as the protection scope of the present invention. The structures, devices and operating methods not specifically described and explained in the present invention shall be implemented according to the conventional means in the art unless otherwise specified and limited.
Claims
1. A highly insulating polyimide composite film precursor solution and a film preparation method thereof, characterized in that: The following steps are involved: Stp100: Preparation of modified carbon nanotube composites: The carbon nanotubes are sequentially subjected to acid treatment and polymer wrapping to obtain modified carbon nanotubes, and the modified carbon nanotubes are dispersed in water to obtain a suspension; the mica powder is pretreated, the pretreated mica powder is added to the suspension, ultrasonically treated for 1 to 2 hours, stirred for 0.5 to 1 hour, and a mixed suspension is obtained; the mixed suspension is rotary evaporated to obtain a modified carbon nanotube composite, wherein the weight ratio of the modified carbon nanotubes, the mica powder and the water in the mixed suspension is 1:1:100; Stp200: prepare precursor solution; The modified carbon nanotube composite material is dispersed in an organic solvent, a protective gas is introduced, ultrasonic treatment is performed for 1 to 2 hours, and stirring is performed for 0.5 to 1 hour to obtain a first mixed solution. A diamine monomer is added to the first mixed solution, and stirring is performed for 0.5 to 1 hour to obtain a second mixed solution. Under the protection of the protective gas, a dianhydride monomer is added to the second mixed solution, and stirring is performed at room temperature for 4 to 8 hours to obtain a precursor solution. Stp300: Preparation of high insulation polyimide composite film: The precursor solution was coated onto a glass plate, which was placed in a drying device and dried at 70°C for 9 hours. The temperature was increased in a stepwise manner, and the glass plate was dried at 100°C, 150°C, 200°C, and 300°C for 1 hour. After drying, the glass plate was cooled to room temperature and demolded with deionized water to obtain a highly insulating polyimide composite film.
2. The highly insulating polyimide composite film precursor solution and the film preparation method thereof according to claim 1, characterized in that: In the Stp100, the carbon nanotubes are multi-walled carbon nanotubes.
3. The highly insulating polyimide composite film precursor solution and the film preparation method thereof according to claim 1, characterized in that: In the Stp100, the carbon nanotubes are sequentially subjected to acid treatment and polymer wrapping, comprising the following steps: Stp101: Mix concentrated sulfuric acid and concentrated nitric acid to obtain a mixed acid solution, wherein the volume ratio of the concentrated sulfuric acid to the concentrated nitric acid is 3:1; Stp102: Disperse carbon nanotubes in a mixed acid solution and perform an ultrasonic treatment at 45kHz for 1 to 2 hours to acid-treat the carbon nanotubes; Stp103: The acid-treated carbon nanotubes were washed with deionized water for multiple times and vacuum dried at 60°C to 80°C for 24 h to obtain acidified carbon nanotubes; Stp104: dissolving the polymer in a solvent to obtain a polymer solution, dispersing the acidified carbon nanotubes in the polymer solution, ultrasonically treating for 1 to 2 hours, removing the solvent, and obtaining modified carbon nanotubes.
4. The highly insulating polyimide composite film precursor solution and the method for preparing the film according to claim 1, characterized in that: In the Stp104, the polymer is one of the following substances: polystyrene, polypropylene; the solvent is one of the following substances: toluene, chloroform.
5. The highly insulating polyimide composite film precursor solution and the film preparation method thereof according to claim 1, characterized in that: In the Stp100, the mica powder is pretreated, comprising the following steps: Stp110: dissolving the surfactant in water to obtain a pretreatment solution; Stp111: Disperse mica powder in the pretreatment liquid, perform ultrasonic treatment for 0.5-1h, stir for 0.5-1h, and centrifuge to obtain mica powder wet material; Stp112: Wash the wet mica powder with deionized water for 3 to 5 times to remove the residual surfactant on the surface of the wet mica powder, and vacuum dry it at 60°C to 80°C for 2 to 4 hours to obtain pretreated mica powder.
6. The highly insulating polyimide composite film precursor solution and the film preparation method thereof according to claim 1, characterized in that: In the Stp110, the surfactant is one of the following substances: sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, and the weight ratio of the surfactant to water is 1:
100.
7. The highly insulating polyimide composite film precursor solution and the film preparation method thereof according to claim 1, characterized in that: In the Stp111, the particle size of the mica powder is in the range of 10 to 100 nm.
8. The highly insulating polyimide composite film precursor solution and the film preparation method thereof according to claim 1, characterized in that: In the Stp200, the organic solvent is N,N-dimethylacetamide, the protective gas is nitrogen, the diamine monomer is one of the following substances: 4,4'-hexafluoroisopropylphthalic anhydride, 4,4'-bisphenol A diamine, 4,4'-biphenyl ether diamine, 4,4'-diaminodiphenylmethane, and the dianhydride monomer is one or more of the following substances: 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 4,4'-oxydiphthalic anhydride, and pyromellitic acid dianhydride.
9. The highly insulating polyimide composite film precursor solution and the film preparation method thereof according to claim 1, characterized in that: In Stp200, the molar ratio of the diamine monomer to the dianhydride monomer is 1:1.